CD56bright natural killer cells and response to daclizumab HYP in relapsing-remitting MS. Issue 2 (April 2015) - Elkins, J.; Sheridan, J.; Amaravadi, L.; Riester, K.; Selmaj, K.; Bielekova, B.; Parr, E.; Giovannoni, G.
Abstract : Objective: To assess the relationship between CD56 bright natural killer (NK) cells and multiple sclerosis (MS) disease activity in patients with relapsing-remitting MS treated with daclizumab high-yield process (DAC HYP). Methods: Data were from patients enrolled in a 52-week randomized, double-blind, placebo-controlled study of DAC HYP and its extension study. Assessments included relationships of CD56 bright NK cell numbers (identified using fluorescence-activated cell sorting) at weeks 4 and 8 with the numbers of new or newly enlarging T2-hyperintense lesions between weeks 24 and 52 and the annualized relapse rate. Results: In DAC HYP–treated patients but not placebo-treated patients, the numbers of CD56 bright NK cells increased over 52 weeks of treatment, and their numbers at weeks 4 and 8 predicted the number of new or newly enlarging T2-hyperintense lesions between weeks 24 and 52 of treatment ( p ⩽ 0.005 for each comparison). Similar but nonsignificant trends were observed between CD56 bright NK cell counts and the annualized relapse rate in DAC HYP–treated patients. DAC HYP–treated patients who showed lower levels of expansion of CD56 bright NK cells still developed fewer new or newly enlarging T2-hyperintense lesions than placebo-treated patients during the first year of treatment. Conclusions: CD56 bright NK cells appear to mediate some of the treatment-related effects of DAC HYP, but their numbers do not account for the full effect of DAC HYP on MS-related outcomes.